Gundala and Gatotkaca in the concept of modern Indonesian superheroes: Comparative analysis of the Indonesian and American superheroes - Deswandito Dwi Saptanto; Maya Kurnia Dewi (Universitas Islam Sultan Agung, 2020)
The superhero universe has always been an attraction in the world of film industry. The birth of superhuman ideas has made people increasingly interested in taking the storyline. This research is a literature study on the existence of a new world in Indonesian cinema that takes the theme of Indonesia's superhero universe competes against the universe of American superheroes. The purpose of this study is to compare Indonesian and American superhero films in order to understand the complete concept of depicting Indonesian superheroes in the process of switching from comics to films comparing with the same concepts in American superheroes. This study employed a descriptive qualitative method by comparing films from the Indonesian superhero universe namely Bumilangit Cinematic Universe and Jagad Satria Dewa Cinematic Universe compared to the American superhero universe namely Marvel Cinematic Universe and DC Cinematic Universe. The results obtained that there were some similarities in the process of character formation in each of the heroes that were created, this could be described with similarity in multiple personalities before and after becoming superheroes, costumes worn, storylines and special effects produced in the film. There were fundamental differences that were seen in the background of Indonesian culture that was different from the concept of American culture. Indonesian superheroes also highlighted Pencak Silat as the original identity and characteristics of Indonesia. This research concluded that a story with a superhero concept had the same story pattern such as a person with a superhero alter ego and deep with heroic storyline even though they were presented by different countries.